Rostovye charakteristiki sportsmena-tennisista i popadaemost' podaci (matematiceskaja model') - Chusainov, V. G.; Semuratov, F. A.; Razumov, D. V. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The rate of scoring is the index showing the achievement of the initial result of a ball-service that is ball-service scoring the so-called "visible" part of the ball-service square. The nature of the rate changing of ball-service scoring depending on the position of the hitting point on the ball (or the length of a sportsman's body) providing the straight-lines of the flying trajectory of a ball was studied. The mathematics dependencies derived in the article may be taken as a basis of instrumentation used in the complex research of the role and the position of the ball-service when constructing tactics and the strategy of a game.